2016
DOI: 10.1242/dev.130369
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of the placenta- and yolk sac-specific tristetraprolin family member ZFP36L3 identifies likely mRNA targets and an unexpected link to placental iron metabolism

Abstract: The ZFP36L3 protein is a rodent-specific, placenta-and yolk sacspecific member of the tristetraprolin (TTP) family of CCCH tandem zinc finger proteins. These proteins bind to AU-rich elements in target mRNAs, and promote their deadenylation and decay. We addressed the hypotheses that the absence of ZFP36L3 would result in the accumulation of target transcripts in placenta and/or yolk sac, and that some of these would be important for female reproductive physiology and overall fecundity. Mice deficient in ZFP36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…However, it seems that Zfp36L3 expresses only in specific tissues (yolk sac and placenta) in certain rodents (rats and mice), while the IRP-IRE system is ubiquitous across vertebrates. In addition, it demonstrated that deletion of the Zfp36l3 in mice stabilized TfR1 mRNA, but counterintuitively, significantly decreased overall TfR1 mRNA expression (Stumpo et al 2016), highlighting the complexity of TfR1 expression regulation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, it seems that Zfp36L3 expresses only in specific tissues (yolk sac and placenta) in certain rodents (rats and mice), while the IRP-IRE system is ubiquitous across vertebrates. In addition, it demonstrated that deletion of the Zfp36l3 in mice stabilized TfR1 mRNA, but counterintuitively, significantly decreased overall TfR1 mRNA expression (Stumpo et al 2016), highlighting the complexity of TfR1 expression regulation.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study uncovered a role for TTP (tristetraprolin) to destabilize TfR1 mRNA (Bayeva et al 2012); however, this study concluded that TTP activity was activated by iron deficiency rather than iron excess and seems to be separate from the IRE-IRP system. A follow-up study highlighted the importance of a TTP-family protein (ZFP36L3) in TfR1 regulation during development (Stumpo et al 2016). However, it seems that Zfp36L3 expresses only in specific tissues (yolk sac and placenta) in certain rodents (rats and mice), while the IRP-IRE system is ubiquitous across vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Expression in the long term cultured ectoderm-and XEN-like cells was compared to these tissue expression data sets from the literature: neural progenitor cells 64 , neural crest cells 65 , yolk sac 66 and a XEN cell line 67 .…”
Section: Articlementioning
confidence: 99%
“…It is the only mouse family member that appears to reside permanently in the cytoplasm, in contrast to the nucleo-cytoplasmic shuttling behavior of the other proteins. A complete KO of Zfp36l3 in mice resulted in decreased neonatal survival rates [11], as well as the accumulation of many transcripts that were stabilized in studies of trophoblastic stem cells derived from the KO mice, many of which are important for placental function.…”
Section: Loss Of Function Mutationsmentioning
confidence: 99%
“…All four of the mouse genes have been knocked out at the “whole body” level, with remarkably different phenotypes; in several cases, cell- and tissue-specific knockouts have been developed as well [11-16]. Results of these studies have pointed to important physiological roles of these proteins in processes as divergent as innate immunity, establishment of the fetal circulation, hematopoiesis, and placental physiology.…”
mentioning
confidence: 99%